Leakage and atmospheric dispersion of CO2 associated with carbon capture and storage projects - Mazzoldi, Alberto (2009)
Climate change is affecting planet Earth. The main cause is anthropogenic emissions of greenhouse gases, the principal one being carbon dioxide, released in the atmosphere as a by-product of the combustion of hydrocarbons for the generation of energy. Carbon capture and storage (CCS) is a technology that would prevent carbon dioxide from being emitted into the atmosphere by safely sequestering it underground. For so doing, CO2 must be captured at large emission points and transported at high pressure to underground reservoirs, where the gas can be injected and stored for thousands of years to come. During surface transportation, leakages from high pressure facilities would pose a risk to the general public, for carbon dioxide is toxic at high concentrations.